PENGEMBANGAN MEDIA MANIPULATIF PUZZLE GAME PADA MATERI KOMBINASI PERMUTASI - Afin Nur Latifa; Reza Kusuma Setyansah; Maya Kristina Ningsih; Ibadullah Malawi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to develop a manipulative puzzle game media on permutation and  combination subject. The puzzle game manipulative media developed in this study consisted of  game board and game card. This research is a development research using a response questionnaire instrument and a validation sheet. This manipulative media development research refers to the model proposed by Plomp which consists of 5 stages, namely 1) the initial investigation stage, 2) design stage, 3) realization stage, 4) evaluation, test, and revision stages, and 5) implementation stage. This research was only carried out until the evaluation and  revision stage. The subjects in this study were 10 prospective mathematics teachers. The techniques of analyzing by Hobri’s. The results of this study from questionnaire response analysis showed that the percentage of media practicality, which was 80%, was in the practical category. Based on analysis data of validation sheet, percentage of media validity is 83% so that is in the valid category. This shows that the manipulative puzzle game media is valid and practical to use in learning activities.